Analysis of Work Environment and Work Discipline on Employee Performance with Job Satisfaction as a Mediating Variable at the Medan Belawan Tax Office Medan Belawan Primary Tax Office - Samuel Alexander Leonardo Sianturi; Husni Muharram Ritonga; Kiki Farida Ferine (Journal of Management, Economic, and Accounting, 2026)
Employee performance is an important factor in supporting the quality of public services, especially at the Medan Belawan Primary Tax Office as an agency that plays a direct role in tax administration and services. This study aims to analyze the effect of work environment and work discipline on employee performance with job satisfaction as a mediating variable. This study uses a quantitative approach with a survey method. The research population consists of all civil servants at the Medan Belawan Primary Tax Office, totaling 100 people, with a saturated sample technique. Data were collected through questionnaires and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the help of the SmartPLS application. The results show that work environment and work discipline have a positive and significant effect on employee performance. In addition, work environment and work discipline also have a positive and significant effect on job satisfaction. Job satisfaction is proven to have a positive and significant effect on employee performance and acts as a mediating variable in the relationship between work environment and employee performance, as well as between work discipline and employee performance. The coefficient of determination shows that the work environment and work discipline can explain 49.6% of job satisfaction, while the work environment, work discipline, and job satisfaction can explain 61.2% of employee performance. The results of this study imply that improving the quality of the work environment, strengthening work discipline, and managing job satisfaction in a sustainable manner are important strategies in improving employee performance at the Medan Belawan Tax Office.